(untitled) (Plant Tissue Culture and Biotechnology, 2025)
Six SSR markers, namely, RM17, RM19, RM25, RM30, RM206 and RM225 were used to study the genetic diversity among the seven rice genotypes which are highly polymorphic, reliable, and have been shown to be linked to important traits in rice. The most alleles were found in locus RM17, whilst the fewest alleles were found in loci RM25 and RM225. The rice varieties Hori and B-11 were shown to have the lowest genetic distance, but various combinations of rice varieties between Lombur, Pokkali, BRRIdhan-29, Kalampazam, and BRRIdhan-47 showed distinct genetic distances. UPGMA dendrogram prefaced partitioning of 7 rice varieties, indigenous Lombur and salt tolerant Pokkali varieties were closely related in one cluster and another cluster containing rest of varieties in one group. It can be concluded that Lombur rice varieties having rich genetic information resources linked with improved agronomic traits and stress tolerance is a significant rice genotypes for sustainable mutation breeding program. Plant Tissue Cult. & Biotech. 34(2): 123-132, 2024 (December)